EFFECTIVENESS OF THE PROGRAM FOR HANDLING UNINHABITABLE HOUSES IN SUKABUMI CITY - Siti Robiah; M. Rijal Amirullah; Andi Mulyadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The title of this research is